Best Answer

35k^2 - 22k + 3 = 0

The factors of 35 are 1, 5, 7, 35

The factors of 3 are 1, 3

We need to multiply two factors which add to a sum of 22

As we can see, 3*5 + 1*7 will add to 22.

However we need -22, which is easily fixed by changing the signs of two of the factors: -3*5 + -1*7 = -22

so to factor the equation would be

(7k-3)(5k-1)=0

To find solutions to the equation, set each expression in the equation equal to 0.

7k-3=0

7k=3

k=3/7

5k-1=0

5k=1

k=1/5

So, k= 3/7 or 1/5

Q: Solve using factoring 35k squared -22k plus 3 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Solve using the quadratic formula

(3x+4)(3x-4)=0 x=±4/3

It can be solved by using the quadratic equation formula.

To find the solution to this equation, you need to rearrange the terms and solve for the variable. 4 = 2b + b^2 can be rewritten as b^2 + 2b - 4 = 0. You can then solve this quadratic equation by factoring, completing the square, or using the quadratic formula.

x2+x-15 = 0 Using the quadratic equation formula: x = 3.405124838 or x = -4.405124838

Related questions

Solve using the quadratic formula

(3x+4)(3x-4)=0 x=±4/3

It can be solved by using the quadratic equation formula.

Using the quadratic equation formula: x = 8.42 or x = -1.42

To find the solution to this equation, you need to rearrange the terms and solve for the variable. 4 = 2b + b^2 can be rewritten as b^2 + 2b - 4 = 0. You can then solve this quadratic equation by factoring, completing the square, or using the quadratic formula.

-34

x2+x-15 = 0 Using the quadratic equation formula: x = 3.405124838 or x = -4.405124838

It means you are required to "solve" a quadratic equation by factorising the quadratic equation into two binomial expressions. Solving means to find the value(s) of the variable for which the expression equals zero.

(x-12)2 using perfect square

x^2 = 64 x = +,- square root of 64 = +,- 8. Thus, x = -8 or x = 8

5x-125 using factoring = -120

2x2-12x-54 = 0 Solve by factoring or using the quadratic equation formula or by completing the square: (2x+6)(x-9) = 0 Therefore: x = -3 or x = 9